Enhancing Students Numeracy Skills in Solving Probability Problems through Realistic Mathematics Education - Edi Susanto; Ali Mahmudi; Chhorn Sereyvuth (Didaktik Matematika, 2024)
Numeracy skills can help students to solve everyday problems. The low numeracy skills of students are caused by not understanding the problem, lack of strategy, and obstacles to evaluating and interpreting the solution to the context. The teacher needs to implement the learning process by using the RME approach, which uses local context and facilitates activity to think mathematically. This study aims to investigate the RME approach in enhancing numeracy skills and to describe the numeracy skills of students in solving problems according to numeracy indicators. The explanatory sequential mixed methods were used to analyze data from tests and interviews. The research subjects were 32 Grade 8 students, and four selected students chose to do the interviews based on each numeracy skills category. The results show a significant difference between the average numeracy skills of students before and after learning with the RME approach. Students with proficient, competent, and basic competencies fulfill the numeracy indicators. Meanwhile, students who need special intervention still have difficulty modeling problems into mathematical representations, incorrectly use the concept of probability, have inappropriate problem-solving strategies, and cannot interpret mathematical solutions in the form of arguments.